Eficiência alimentar e características da carcaça e da carne de novilhos de diferentes genótipos terminados em dois sistemas alimentares. - Nunes, Marcelo Henrique Giordano (2011)
The objective of this study was to evaluate feed efficiency and carcass and beef quality of pure and crossbred genotypes, as well as the possible influence of the finishing system on the beef physical-chemical and sensory traits. Steers of six different genotypes, Aberdeen Angus (ANAN), Hereford (HHHH), Nellore (NENE), Aberdeen Angus x Nellore (ANNE), Aberdenn Angus x Hereford (ANHH) and Aberdeen Angus X Caracu (ANCR) were evaluated during finishing in two different systems: feedlot or cultivated pasture. The steers entered the finishing with an average age of 19.8 ± 0.91 months. Animals kept in feedlot received a diet containing 40% concentrate and 60% of forage on a dry matter basis. The roughages used were corn and sorghum silage mixed in 50:50 ratio. All supplied feed and the leftovers were weighed daily to estimate daily intake of confined steers. Cattle finished on pasture was kept in a paddock with cultivated oats and ryegrass. The slaughter criterion was a subcutaneous fat thickness of at least 3 mm, measured at the weighing days by ultrasound. Significant differences in feed efficiency were found between studied genotypes. The animals of HHHH breed group were superior to the ANAN and NENE animals in the residual feed intake evaluation obtaining the respective values of -0.92 kg versus 0.73 and 0.70 kg. For feed conversion the HHHH shower a smaller amount of feed intake per kilogram of weight gain when compared to ANNE, ANCR and NENE (6.0 vs. 9.4, 8.5 and 10.9 kg, respectively). The HHHH had the lowest dry matter intake, 7.4 kg, and did not differ only of the NENE (8.5 kg). It was observed a smaller slaughter weight in the NENE (403 kg), while ANNE and ANCR animals showed higher values for chilled carcass weight (272 and 256 kg, respectively). In assessing the primary cuts of the carcass, the NENE presented the lowest rib weight, 14 kg, when compared to others genotypes. Regarding beef quality, the ANCR breed group presented tenderer steaks than ANNE and NENE groups in the evaluation of shear force (3.7 vs 5.9 e 6.9kgf, respectively). In sensory toughness attribute, the beef of ANCR, ANHH and HHHH animals was considered tenderer than NENE animals. Caracu breed can be used as an alternative to zebu in crossing with British breeds showing comparable levels in quantitative aspects of carcass, but with higher beef tenderness when compared to zebu breeds. In this experiment conditions, the NENE showed low productivity and also poor beef and carcass quality; nevertheless, it had superior performance in the crossbreeding with Aberdeen Angus.